THE ROLE OF GLUTATHIONE IN SPERM RESISTANCE TO CRYOPRESERVATION - Santos, Dario (2019)
The reduced form of glutathione (GSH), the most abundant intracellular antioxidant thiol in mammalian systems, participates in diverse reactions, including reacting with reactive oxygen (ROS) and nitrogen species (RNS), electrophiles, and other non-enzymatic antioxidant compounds, as well as protein deglutathionylation. GSH is a key-molecule in oxidative stress balance, as GSH effectively scavenges free radicals and other reactive oxygen species. Among its multiple roles, GSH is required for mitochondrial function and integrity. Most of the cellular content of GSH (85–90%) is present in the cytosol, while the remainder can be found in several different organelles (such as the mitochondria, nuclear matrix, and peroxisomes). GSH transcription or activity is triggered in cells submitted to an oxidant or thermal stress, among other stimuli. However, due to their cellular characteristics, sperm are poorly endowed to react against oxidative stress. Both their scant cytosol content and transcriptional ability limits their production of GSH, rendering the sperm particularly sensitive to damage from the accumulation of reactive oxygen species in the medium. Moreover, the spermatozoon presents some weaknesses that make it an easy target for oxidative stress, such as the high levels of polyunsaturated fatty acids in the sperm plasmatic membrane, or the highly compacted mitochondrial sheet. Notwithstanding, the seminal plasma contains high activities of several oxidative stress enzymes, which partially deflect spermatozoon sensitivity while bathed in this fluid. This sensitivity is a major factor to consider during sperm collection and cryopreservation. Oxidative stress impacts sperm function by interfering with plasma membrane fluidity, inactivating membrane-enzymes, increasing its permeability for non-specific ions, affecting key intracellular enzymes, decreasing motility and damaging paternal DNA, leading to a loss of sperm fertility. In recent years, the incorporation of glutathione or other antioxidant molecules to the extender media has been assayed in multiple species to foster sperm survival for semen preservation, in particular for freezing-thawing procedures. In this chapter, we will revise the part played by glutathione in male fertility and semen homeostasis, as well as addressing the role of GSH in sperm function and GSH-based strategies to improve sperm cryopreservation.